Ushebtis of the Third Intermediate Period from the Chapel of Hatshepsutin the Queen’s temple at Deir el-Bahari - Agnieszka Makowska (Polish Archaeology in the Mediterranean, 2016)
A collection of 619 whole and fragmentary ushebti figurines dating from the ThirdIntermediate Period was recovered between 2004 and 2007 by the Polish team excavating in theChapel of Hatshepsut, an integral part of the Queen Pharaoh’s mortuary temple in Deir el-Bahari.The figurines include objects of faience, clay and painted clay, all relatively small and roughlymodelled. They represent a category of objects that is seldom published separately. The paperpresents a typology of the ushebtis based primarily on the material from which they were produced,discussing their chronology and find contexts as well.